Deciphering Victim Precipitation: A New Lens on Sentencing for Sexual Violence Cases - Elisna, Elisna (Jurnal Negara Hukum: Membangun Hukum Untuk Keadilan, 2023)
Victim precipitation, concerning criminal victims, cannot be construed as the victim’s contribution that incited the perpetrator to commit the crime. Attributing any role to the victim in the victimization they experienced places an undue burden of responsibility on them, leading to further suffering. Through normative legal research, which entails the evaluation of legal norms and regulations with both statutory analysis and a case study approach, this article tries to present a viewpoint that underscores how arguments attributing the victim’s role as a motivating factor for the offender cannot serve as a basis for reducing sanctions against the perpetrator. Granting reduced penalties based on the victim’s supposedcontribution to the victimization process undermines the victim’s hope for substantial punishment for the offender. The concept of victim precipitation must be interpreted not as grounds for mitigating thepunishment of sexual violence offenders but rather as a policy approach to prevent sexual violence by adopting effective preventive measures.